Tuberculosis Treatment Completion in a United States/Mexico Binational Context - Valencia, Celina I.; Ernst, Kacey; Rosales, Cecilia Ballesteros (Frontiers in Public Health, 2017)
Background Tuberculosis (TB) remains a salient public health issue along the U.S./Mexico border. This study seeks to identify the social and structural factors, which are associated with TB disease burden in the binational geographic region. Identification of barriers of treatment completion provides the necessary framework for developing evidence-based interventions that are culturally relevant and context specific for the U.S./Mexico border region. Methods Retrospective study of data extracted from medical charts (n = 439) from Yuma County Health Department (YCHD) (n = 160) and Centro de Salud San Luis Río Colorado (n = 279). Patients currently accessing TB treatment at either facility were excluded from the study. Chi-square, unadjusted odds ratios, and logistic regression were utilized to identify characteristics associated with successful TB treatment in this population. Findings The study population was predominantly male (n = 327). Females were more likely to complete TB treatment (OR = 3.71). The absence of drug use and/or the absence of an HIV positive diagnosis were found to be predictors of TB treatment completion across both clinical sites. Forty-four percent (43.59%) (n = 85) TB patients treated at CDS San Luis did not complete treatment versus 40.35% (n = 49) of TB patients who did not complete treatment at YCHD. Moving from the area or being deported was the highest category (20.78%) for incomplete TB treatment in the population (n = 64) across both clinical sites.